ANALISIS FAKTOR YANG MEMPENGARUHI NILAI INFORMASI LAPORAN KEUANGAN: (Studi Pada Dinas Pekerjaan Umum dan Penataan Ruang Kabupaten Cilacap) - Rahman, Kristanti; Widyastuti, Dewi (JURNAL EKONOMI, 2022)
The purpose of this research is to analyze the factors that affect the value of financial reporting information. Factors that affect financial reporting information value is measured by the variable quality of human resources, utilization of technology and information, internal control systems. The research approach used is associative. The respondents in this study 32 respondents. The sampling techniques used in this research is the saturated samples. Data collection is carried out by means of a detailed questionnaire. Research data was processed using SPSS. The research method used was multiple linear regression. Human resources impact the value of the information financial statements. The utilization of information technology and the effect on the value of the information financial statements. The system of internal control to the value of the information financial statements. Human resources, internal control system technology and information utilization simultaneously impact the value of financial report information